African migration narratives politics, race, and space - Iheka, Cajetan Nwabueze; Taylor, Jack, 1982- (Rochester studies in African history and the diaspora., 2018)
Examines the representations of migration in African literature, film, and other visual media, with an eye to the stylistic features of these works as well as their contributions to debates on migration--Provided by publisher.